Noncontiguous finished genome sequence and description of Weeksella massiliensis sp. nov. (November 2015) - Sankar, S.A.; Lo, C.I.; Fall, B.; Sambe-Ba, B.; Mediannikov, O.; Diallo, I.; Labas, N.; Faye, N.; Wade, B.; Raoult, D.; Fournier, P.-E.; Fenollar, F.
Abstract: Strain FF8 T (= CSUR P860 = DSM 28259) was isolated in Dakar, Senegal, from the urine of a 65-year-old man with acute cystitis. This strain shows a similarity of sequence of 16S rRNA of 98.38% with Weeksella virosa, and its GenBank accession numbers areHG931340 andCCMH00000000 . Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry analysis had a poor score, ranging from 1.32 to 1.56, that did not allow identification of the bacterium. Using a polyphasic study made of phenotypic and genomic analyses, strain FF8 T was a Gram-negative, aerobic rod and a member of the family Flavobacteriaceae . The sequenced genome is 2 562 781 bp with one chromosome but no plasmid. It exhibits a G + C content of 35.9% and contains 2390 protein-coding and 56 RNA genes, including a complete rRNA operon. On the basis of these data, we propose the creation of Weeksella massiliensis sp. nov.